Organic-Inorganic Hybrid Solar Cells - Strachala, David; Hylský, Josef; Kadlec, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
The purpose of the presented work is to find an optimal way for the preparation of the organic-inorganic hybrid solar cells based on perovskite structure CH3NH3PbI3-2Cl2 /PC61BM. The main idea of the work is to create an eight solar cell samples with the highest possible conversion efficiency and stable structure. Conversion efficiency of created samples reached approximately ηMAX = 2, 5 %. Samples were futher analyzed and based on that were implemented other techniques for their improvement.
Keywords: Organic – inorganic hybrid solar cells; perovskite solar cells; conversion efficiency